Forest Inventory Using Satellite Optical and Radar Remote Sensing with Ancillary Data - Mat Lela, Mohamed Said (Fakulti Ukur dan Harta Tanah, 1993)
particularly the deforestation of the world's rain forest. To this end there is a need for accurate detection, inventory, monitoring and management for forest resources. Optical remote sensing methods have successfully being utilised in the inventory of forest species. The incorporation of ancillary data with remotely sensed data for digital data analysis in determining forest species distribution have further increased the classification accuracy. Ulaby et al. (1982) suggested that, in order to achieve high correct classification rates, it is necessary to have uninterrupted (cloud free) coverage of the area under investigation for successive passes of the satellite. This paper set out to examine the extent to which satellite imaging radar or synthetic aperture radar (SAR) augment the information content of satellite optical imagery in forest classification and to what extent does the transformation of spectral data and the incorporation of ancillary data improves the classification of forest trees.